Feasibility of irrigation monitoring with cosmic-ray neutron sensors - Brogi, Cosimo; Bogena, Heye Reemt; Köhli, Markus; Huisman, Johan Alexander; Hendricks Franssen, Harrie-Jan; Dombrowski, Olga (Geoscientific instrumentation, methods and data systems, 2022)
Accurate soil moisture (SM) monitoring is key in irrigation as it can greatly improve water use efficiency. Recently, cosmic-ray neutron sensors (CRNSs) have been recognized as a promising tool in SM monitoring due to their large footprint of several hectares. CRNSs also have great potential for irrigation applications, but few studies have investigated whether irrigation monitoring with CRNSs is feasible, especially for irrigated fields with a size smaller than the CRNS footprint. Therefore, the aim of this study is to use Monte Carlo simulations to investigate the feasibility of monitoring irrigation with CRNSs.